О стойкости уменьшенных моделей блочных шифров к линейному криптоанализу - Долгов, В. И.; Руженцев, В. И. (ХНУРЭ, 2008)
The reduced scale models of modern block ciphers are proposed. The security of these models to linear cryptanalysis are checked with using of various testing methods. The conclusions about using the various methods of testing the security from linear cryptanalysis of modern block ciphers are made.
Keywords: блочный шифр; линейний криптоанализ